Security State of Wireless Networks - Vindašius, A. (Elektronika ir Elektrotechnika, 2006)
Mass deployment of wireless networks faces many security issues, which tends to be unique and less understandable since most of this kind of threats doesn’t exist in wired networks at all. Many serious problems arise concerning privacy and private network separation, since data are being transmitted trough shared and freely accessible wireless medium. The main security problems and vulnerabilities concerning wireless networks are shortly addressed. This paper presents results and analysis of passive 2,4 GHz band scanning in Vilnius in order to discover wireless IEEE 802.11b/g standard networks and identify the main parameters which show the general view of security state of wireless networks. The data obtained from analysis indicates that main security threats are experienced by wireless networks due to disabled link layer encryption. The other problem is considering access points as trusted nodes in wired local area networks. Ill. 3, bibl. 12 (in English; summaries in English, Russian and Lithuanian).